Centralizationandefficientmechanismfor administrativemanagement - Márquez, Mariana Alvarado; Olivero Arias, Edison (Revista Universidad de Guayaquil, 2015)
Itis currently oneof the requirements for the validation of administrative processes optimal useof the elements of time management and intended for activation there of; this proposal seeks,from the establishment of organizational and institutional settings implemented in the Ecuadorian public sector to that end, review the application of a model of decentralized management , and other centralized, where the latter, however,the autonomy of operations offered byt he previous, it allows better control, especially in instances related to the allocation of furniture and other resources needed tocarry out certain tasks assets.